2017
DOI: 10.1590/0102.3772e33314
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre Fluência e Compreensão Leitora em Escolares com Dificuldades de Aprendizagem

Abstract: RESUMO A capacidade para ler e compreender textos é fundamental tanto em nossa vida diária como no contexto educativo. Considerando esse aspecto, o objetivo deste estudo foi comparar a fluência e a compreensão de leitura de escolares do segundo para o quinto ano do ensino fundamental com e sem dificuldades de aprendizagem. Participaram oitenta escolares divididos em oito grupos: GI a GIV (escolares sem dificuldades de aprendizagem); GV a GVIII (escolares com dificuldades de aprendizagem). Por meio da leitura o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
5
0
3
Order By: Relevance
“…Thus, the results confirm the findings of the scientific literature on the subject (Cunha & Capellini, 2016;Cunha, Martins, & Capellini, 2017Pacheco & Santos, 2017;Lúcio, Lima, Jesuino, & Rueda, 2018), who identified that students of more advanced years and, therefore, with more schooling, have better score in the Cloze test and, consequently, better level of reading comprehension. Some authors (Morais, Leite, & Kolinsky, 2013;Pacheco & Santos, 2017) explain that the difference in level of reading comprehension between school years is understood by changes in reading abilities over time.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the results confirm the findings of the scientific literature on the subject (Cunha & Capellini, 2016;Cunha, Martins, & Capellini, 2017Pacheco & Santos, 2017;Lúcio, Lima, Jesuino, & Rueda, 2018), who identified that students of more advanced years and, therefore, with more schooling, have better score in the Cloze test and, consequently, better level of reading comprehension. Some authors (Morais, Leite, & Kolinsky, 2013;Pacheco & Santos, 2017) explain that the difference in level of reading comprehension between school years is understood by changes in reading abilities over time.…”
Section: Discussionsupporting
confidence: 88%
“…According to the national and international literature, access to narrative texts is present in the child's life from moments prior to schooling, since contact with this textual genre occurs through storytelling, which makes this structure familiar to the child. On the other hand, contact with expository texts is formally carried out in the more advanced years, since the expository textual gender is used to transfer information, as a tool for the formal learning of specific contents, which suggests that students have already developed basic skills to make them fluent readers and able to understand and interpret denser content (Nalom et al, 2015;Cunha, Martins, & Capellini, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Na avaliação da fluência de leitura dos escolares do Ensino Fundamental, os estudos de Celeste et al (2018) e Martins e Capellini (2019), ambos de desenho transversal, avaliaram o desempenho em fluência leitora de escolares sem dificuldades leitoras e verificaram a evolução da fluência leitora de acordo com o avanço da escolaridade. Estudos realizados com a mesma faixa escolar supracitada, avaliando a diferença entre o desempenho em fluência de leitura dos escolares com e sem dificuldades, demonstrou diferenças entre os grupos, no qual os escolares com dificuldades apresentaram maior número de erros e menores valores médios de taxa e acurácia de leitura de palavras, pseudopalavras e textos (Cunha et al, 2017;Kawano et al, 2011).…”
Section: Introductionunclassified